Scale and impact of the illegal leopard skin trade for traditional use in southern Africa - Naude, Vincent Norman (Department of Biological Sciences, 2021)
While leopards (Panthera pardus) currently occupy the most extensive geographic range of all large felids, they are also suffering the highest rate of current range loss amongst large terrestrial carnivores. This is primarily because most leopards still range outside of formally protected areas where they are exposed to the full suite of anthropogenic threats affecting carnivores including habitat loss, prey depletion, conflict with humans, and commercial harvest for body parts. The extensive use of leopard derivatives among traditional healers, royalty, and culturo-religious groups poses a known but poorly understood threat to leopards. Sociopolitical sensitivities surrounding cultural identity and the illegality of much of this use have impeded an objective assessment of both the drivers and impacts of this threat. Through a multi-disciplinary approach, this thesis describes the drivers of illegal leopard skin trade among a significant portion of traditional users in South Africa, quantifies the extent of this trade across the southern African region and assesses its impact on local leopard populations. Together these findings seek to address the lack of conservation- and policy-relevant data regarding the impact and scale of the trade for traditional use in South Africa. Followers of the recently established ‘Shembe' Church, with its estimated membership of over four million in South Africa, represent the foremost culturo-religious users of illegal leopard skins in the world. Following the introduction of a faux skin alternative, I used longitudinal surveys to explore the drivers of authentic skin desirability and possession amongst faux skin recipients. While demand for authentic skins decreased, and faux alternatives were generally considered satisfactory, 27% still expressed a desire for an authentic skin, and 15% had acquired one in the three years since receiving their faux skin. Both desiring and having obtained an authentic skin were best explained by improved economic status and the perceived weakness of law enforcement. The combined demand of all Shembe followers cannot be sustained by the estimated extant leopard population of South Africa, and it is predicted that traders must be sourcing leopards from surrounding range states to meet local demands. To investigate this, I created a genetic reference database of leopards across southern Africa (1,452 individuals) and using DNA-based assignment tests, inferred the geographic origins of illegally traded skins sourced within southern Africa. Smoothed continuous assignment techniques revealed leopard source ‘hotspots' in southwestern Zimbabwe, southern Mozambique and along the eastern borders of South Africa confirming suspicions that the illegal leopard skin trade for traditional use in South Africa is transnational. A similar distribution of leopard source populations was identified from leopard parts obtained in traditional wildlife markets and a large-scale confiscation from a single trader. Together, this suggests the regional trade in leopard parts has been syndicated with predictable harvesting and trade routes into the South African consumer market. Genotyping across all trade samples (237 individuals) revealed a clear bias towards males despite reported sex-ratios being female-biased for natural free-ranging populations. To understand the ecological cost of this sex-biased exploitation of leopards, I compared the spatial, genetic, and demographic data of two South African leopard populations with markedly different histories of anthropogenic mortality. Home-range overlap, parentage assignment, and spatio-genetic autocorrelation showed that extensive historical exploitation, linked to Shembe and other traditional trade, has reduced subadult male dispersal, thereby facilitating opportunistic male natal philopatry. The resultant kinclustering in males is comparable to that of females in the well-protected reserve and has promoted localised inbreeding. Together these results demonstrate novel evidence linking significant ecological consequences to an underestimated, transnational, and syndicated illegal leopard skin trade driven by demand for traditional and religious use in South Africa. These findings are translatable to all leopard populations threatened by exploitation and emphasise the importance of long-term monitoring of leopard populations within protected areas and improving management interventions to mitigate these effects. Interventions such as anti-poaching can be focussed on the ‘hotspots' identified in this study while protected area management should prioritise the maintenance of dispersal corridors to promote in situ recovery of exploited populations. Lastly, demand reduction strategies such as the continued provisioning of suitable alternatives, together with improved education and increased enforcement, are essential to addressing the growing culturo-religious demand for leopard products contributing to the illegal harvest and trade in this iconic large predator. Success will depend on finding the balance between an improved transnational policy which effectively conserves wild leopard populations and maintaining respect for cultural practices